The Humanization of Accountability: A New Paradigm for Waqf Management - Nurngaini, Siti; Wasyith, Wasyith; Aniqoh, Nur Aini Fitriya Ardiani (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
The practice of waqf accountability in general often places excessive emphasis on technical and financial measurements, thereby neglecting the humanitarian mission that constitutes the very essence of waqf institutions. This paper seeks to address that limitation by proposing the idea of a “humanization of waqf accountability”, an integrated framework grounded in the prophetic social thought of Kuntowijoyo. The framework rests upon three main pillars. First, active community participation, which positions beneficiaries not as passive recipients but as empowered subjects. Second, social justice, which redefines waqf as an instrument for inclusive and sustainable development rather than merely a charitable activity. Third, community well-being, regarded as the ultimate goal, is measured through holistic indicators of human dignity. By integrating these pillars, this comprehensive paradigm not only aligns waqf governance with its ethical foundations but also responds to contemporary challenges, such as the need for beneficiary-centered management and transparent reporting. In essence, this human-oriented approach provides a pathway for waqf institutions to enhance their social impact, build trust among stakeholders, and fulfill their mandate in realizing sustainable community development more effectively.